+0  
 
0
236
2
avatar

log4 6 + log4 (x + 1) = 2

Guest Apr 4, 2017

Best Answer 

 #2
avatar+87301 
+2

log4 6 + log4 (x + 1) = 2    

 

We can write

 

log4 [6 * (x + 1) ]  = 2

 

In exponential form, we have

 

4^2   =  6 (x + 1)    simplify

 

16 = 6x + 6      subtract 6 from both sides

 

10  = 6x      divide both sides by 6

 

10/ 6  = x  =   5/3

 

 

cool cool cool

CPhill  Apr 4, 2017
 #1
avatar
+1

Solve for x:
(log(6))/(log(4)) + (log(x + 1))/(log(4)) = 2

Rewrite the left hand side by combining fractions. (log(6))/(log(4)) + (log(x + 1))/(log(4)) = (log(6) + log(x + 1))/(log(4)):
(log(6) + log(x + 1))/(log(4)) = 2

Multiply both sides by log(4):
log(6) + log(x + 1) = 2 log(4)

Subtract log(6) from both sides:
log(x + 1) = 2 log(4) - log(6)

2 log(4) - log(6) = log(4^2) + log(1/6) = log(16) + log(1/6) = log(16/6) = log(8/3):
log(x + 1) = log(8/3)

Cancel logarithms by taking exp of both sides:
x + 1 = 8/3

Subtract 1 from both sides:
Answer: | x = 5/3

Guest Apr 4, 2017
 #2
avatar+87301 
+2
Best Answer

log4 6 + log4 (x + 1) = 2    

 

We can write

 

log4 [6 * (x + 1) ]  = 2

 

In exponential form, we have

 

4^2   =  6 (x + 1)    simplify

 

16 = 6x + 6      subtract 6 from both sides

 

10  = 6x      divide both sides by 6

 

10/ 6  = x  =   5/3

 

 

cool cool cool

CPhill  Apr 4, 2017

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.